Indian Ocean Traffic: Introduction - Lola Sharon Davidson; Stephen Muecke (PORTAL: Journal of Multidisciplinary International Studies, 2012)
Like the Mediterranean, the Indian Ocean has been a privileged site of cross-cultural contact since ancient times. In this special issue, our contributors track disparate movements of people and ideas around the Indian Ocean region and explore the cultural implications of these contacts and their role in processes that we would come to call transnationalization and globalisation. The nation is a relatively recent phenomenon anywhere on the globe, and in many countries around the Indian Ocean it was a product of colonisation and independence. So the processes of exchange, migration and cultural influence going on there for many centuries were mostly based on the economics of goods and trade routes, rather than on national identity and state policy.